2018
DOI: 10.1155/2018/7149835
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Triple Cropping System to Four Crops Pattern: An Approach of Enhancing System Productivity through Intensifying Land Use System in Bangladesh

Abstract: Changing three crops pattern to four crops can play a potential role for achieving countries food security. With this view to increase crop productivity, production efficiency, land use efficiency, and economic return through intensifying cropping intensity as well as crop diversity by transforming three crops pattern to four crops, the experiment was conducted in High Ganges River Floodplain Soils under the Agro-Ecological Zone (AEZ) 11 at Pali, Durgapur, under the Multilocation Testing Site, Puthia, Rajshahi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Cropping system intensification from double (rice-rice or rice-wheat) to triple cropping system (Wheat-Mungbean-T. Aman) increased the system REY by 10-75% in the High Ganges River Floodplain and Madhupur tract of Bangladesh [5,32,33]; three times more in the active Brahmaputra-Jamuna Floodplain Chars of Bangladesh [34], but 42% more wheat equivalent yield (WEY) in India [35], as well 82% higher system REY when compared to double to four crop-based systems [36]. In other, reported that cropping system intensification from three to four crop-based system increased system REY by 38-44% across the different agroecological zones of Bangladesh [37][38][39], similar to our study, whereas it was lower by 26% [40] and much higher (81%) as reported by Islam et al [41] compared to our study. In the recent, Saha et al [42] reported cropping system intensification increased 211 to 360% more REY by two to four crop based cropping system in the salt-affected coastal zones of Bangladesh.…”
Section: Crop and System Rice Equivalent Yieldmentioning
confidence: 99%
“…Cropping system intensification from double (rice-rice or rice-wheat) to triple cropping system (Wheat-Mungbean-T. Aman) increased the system REY by 10-75% in the High Ganges River Floodplain and Madhupur tract of Bangladesh [5,32,33]; three times more in the active Brahmaputra-Jamuna Floodplain Chars of Bangladesh [34], but 42% more wheat equivalent yield (WEY) in India [35], as well 82% higher system REY when compared to double to four crop-based systems [36]. In other, reported that cropping system intensification from three to four crop-based system increased system REY by 38-44% across the different agroecological zones of Bangladesh [37][38][39], similar to our study, whereas it was lower by 26% [40] and much higher (81%) as reported by Islam et al [41] compared to our study. In the recent, Saha et al [42] reported cropping system intensification increased 211 to 360% more REY by two to four crop based cropping system in the salt-affected coastal zones of Bangladesh.…”
Section: Crop and System Rice Equivalent Yieldmentioning
confidence: 99%
“…As per the Bangladesh Bureau of Statistics (BBS, 2020), around 4125 thousand hectare and 1867 thousand hectare of land remain under double and triple-cropped areas respectively, which means that 50.77% and 20.98% of the net cropped area in Bangladesh has avenues partly or a greater part to be brought under quadruple cropping system. The area of cropland is declining, that's why there is no alternate option of horizontal extension but intensifying land use system through by growing more crops or multiple cropping on the same piece of land in a calendar year [17]. However, agriculture is heading towards a new example to address the country's food security a concerned issue of Bangladesh [18].…”
Section: Things To Do To Increase Cropping Intensitymentioning
confidence: 99%
“…This newly adopted cropping system may increase farm income while creating job opportunities, alleviating poverty, and ultimately creating positive changes in the farmers' livelihoods. Reports have shown that the four crop-based cropping systems increased the rice equivalent yield up to 20-46% and the gross margin up to 30-41% over the existing lentil-jute-aman rice and boro-fallow-aman rice systems [4,5]. However, to acquire optimal performances in terms of yield, economic return, and soil health under the four crop-based cropping systems, the optimal fertilizer rate should be determined [6].…”
Section: Introductionmentioning
confidence: 99%